2022
DOI: 10.1155/2022/9137706
|View full text |Cite|
|
Sign up to set email alerts
|

A Meta-Analysis of CT as a Tool for Diagnosing and Treating Shoulder Joint Bankart Injuries

Abstract: Objective. The shoulder joint is the most flexible joint in the human body. It is a typical multiaxial ball-and-socket joint. The humeral head is approximately spherical, and the glenoid is small and shallow. This article mainly discusses the application value of computerized tomography (CT) in the early diagnosis of skeletal Bankart injury of the shoulder joint. Methods. The chemical quality was evaluated according to the physical therapy evidence database PEDro scale. The literature quality evaluation scale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%